Density functional study of the 5-methylcytosine tautomers - Sambrano, JR; Souza, Aguinaldo Robinson de [UNESP]; Queralt, J. J.; Olive, M.; Andres, J. (Elsevier B.V., 2001)
B3LYP/6-31++G** calculations to study seven tautomers of 5-methylcytosine in aqueous media have been carried out. Optimized geometries and relative stabilities for the different tautomers have been calculated in the gas phase, including interaction with two discrete water molecules and taking into account the solvent effects by using the self-consistent reaction field theory. The role of specific and bulk contributions of solvent effect on the observable properties of the 5-methylcytosine is clarified. The amino-oxo form is the most abundant tautomer in aqueous media. A reaction pathway connecting amino-oxo and amino-hydroxy forms along the corresponding transition structures has been characterized. Good agreement between theoretical and available experimental results of harmonic vibration frequencies is found. (C) 2001 Elsevier B.V. B.V. All rights reserved.